2008 IEEE Nuclear Science Symposium Conference Record 2008
DOI: 10.1109/nssmic.2008.4774139
|View full text |Cite
|
Sign up to set email alerts
|

Improving light extraction from heavy inorganic scintillators by photonic crystals

Abstract: Abstract-The impact of photonic crystal (PhC) slabs on the extraction of light from the heavy inorganic scintillators LuYAP and LYSO is evaluated by combining numerical transmission calculations of a scintillator with PhC coupling face with simulations of the light propagation inside the scintillator. The transmission of the scintillator-PhC coupling face is determined by means of a scattering-matrix algorithm. The PhC slab is assumed to consist of a bulk material with a triangular pattern of air holes that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The statistical limit on timing performance showed inverse relationships between the CRLB and the N and τd dependence for photon statistics and decay time, respectively. This relationship is well known and has been previously reported in [Gundacker et al 2013a, Fishburn et al 2010, Hyman et al 1964, Kronberger et al 2010]. Calculated timing performance was found to improve linearly with SPTR.…”
Section: Resultssupporting
confidence: 77%
“…The statistical limit on timing performance showed inverse relationships between the CRLB and the N and τd dependence for photon statistics and decay time, respectively. This relationship is well known and has been previously reported in [Gundacker et al 2013a, Fishburn et al 2010, Hyman et al 1964, Kronberger et al 2010]. Calculated timing performance was found to improve linearly with SPTR.…”
Section: Resultssupporting
confidence: 77%
“…The photons in our setup are produced with a Cs137 gamma source. Other parameters necessary for photon generation by gamma excitation, like the photo-electric cross section, the gammaabsorption length, and the emission spectrum, were taken from the work of [39].…”
Section: Light Yield Measurements For the Adaptation Of Slitrani Crys...mentioning
confidence: 99%
“…Parameters used in our SLITRANI simulation setup. Parameters were taken from the work of [38] and [39]. walls and different contact agents.…”
Section: Light Yield Measurements For the Adaptation Of Slitrani Crys...mentioning
confidence: 99%
“…We have already shown in [8] that for an emission point in the center of a -mm LSO crystal ( , mm) coupled to a photodetector with silicon grease of , the maximum time spread between the shortest path-length photon, emitted forward along the crystal axis, and the longest path-length photon, emitted backwards at the total reflection angle on the lateral faces, is given by ps (2) not considering multiple reflections on the extraction face. Simulation shows that without a PhC, nearly 50% of the photons are reflected at the first incidence and reappear for several times (if not absorbed) with a delay ranging from 243 and 384 ps times the number of recurrences of the light rays on the coupling face to the photodetector.…”
Section: Effect Of Phcs On Light Propagation Modes In a Scintillmentioning
confidence: 99%
“…S EVERAL years ago, we identified photonic crystals (PhCs) as a tool with a high potential to significantly improve the performance of scintillator-based detectors [1], [2]. We have shown that well-designed PhCs can enhance the light output of dense scintillators with a high refractive index (between 1.8 and 2.2 for the majority of scintillators) by a large factor ( 2 in air and by at least 50% in grease) [3], [4].…”
Section: Introductionmentioning
confidence: 99%